Hubungan Penggunaan Kontrasepsi Suntik Tiga Bulanan selama Satu Tahun dengan Peningkatan Tekanan Darah - Ardiansyah, Ardiansyah; Fachri, Muhammad (Universitas Ahmad Dahlan, 2017)
Background: Increased blood pressure is the change in blood volume or blood vessel elasticity systole and diastole increased 10 mmHg or more, as measured by sphigmomanometer. Increased blood pressure has multifactorial causes, one of is the use of injectable hormonal contraception. This study aims to describe the prevalence of elevated blood pressure in the study subjects and relationships using injectables three months for one year with an increase in blood pressure. Method: This study used a cross-sectional study. Sampling of 80 respondents with consecutive sampling technique. The study was conducted of injectables acceptor three months for one year, data analysis using Chi-square test. Results: Most of the results obtained have increased blood pressure as much as 58.8% and the results of bivariate analysis using Chi-square test is known that there is a significant relationship between the variables use of injectables (p value <0.05) with an increase in blood pressure. Conclusion: There was a relationship significant between the use of injectables contraception to the increase in blood pressure